Calcium Spiking Patterns and the Role of the Calcium/Calmodulin-Dependent Kinase CCaMK in Lateral Root Base Nodulation of Sesbania rostrata - Capoen, Ward (American Society of Plant Biologists, 2009)
Nodulation factor (NF) signal transduction in the legume-rhizobium symbiosis involves calcium oscillations that are instrumental in eliciting nodulation. To date, Ca(2+) spiking has been studied exclusively in the intracellular bacterial invasion of growing root hairs in zone I. This mechanism is not the only one by which rhizobia gain entry into their hosts; the tropical legume Sesbania rostrata can be invaded intercellularly by rhizobia at cracks caused by lateral root emergence, and this process is associated with cell death for formation of infection pockets. We show that epidermal cells at lateral root bases respond to NFs with Ca(2+) oscillations that are faster and more symmetrical than those observed during root hair invasion. Enhanced jasmonic acid or reduced ethylene levels slowed down the Ca(2+) spiking frequency and stimulated intracellular root hair invasion by rhizobia, but prevented nodule formation. Hence, intracellular invasion in root hairs is linked with a very specific Ca(2+) signature. In parallel experiments, we found that knockdown of the calcium/calmodulin-dependent protein kinase gene of S. rostrata abolished nodule development but not the formation of infection pockets by intercellular invasion at lateral root bases, suggesting that the colonization of the outer cortex is independent of Ca(2+) spiking decoding.